STRATEGI PENGEMBANGAN DESA WISATA BEJIHARJO SEBAGAI UPAYA UNTUK MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN - , MUHAMAD ARIF ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Many communities in various parts of Yogyakarta tourism awareness has been proven by the various tourist village offers all the uniqueness of each. In Gunungkidul example, currently has one of the area Gunungkidul popular tourist village is the Village Tourism Bejiharjo with natural beauty it offers. This tourist village provides a new option in the area tourist activities such Gunungkidul Caving, Cave Tubing, Rafting and Offroad. Village tourism proved successful to reduce the number of unemployed in the region. Village tourism has Bejiharjo alamyang extraordinary wealth and supported by public awareness of the potential of the village. Bejiharjo Tourism Village is one successful example of the persistence of communities to manage their village and sell all the activities that engage residents to participate in serving the tourists who come to this tourist village. Research conducted at the Tourism Village Bejiharjo conducted to determine how rural tourism has become a leading tourist village, whatever the promotion is done, development is being done and analyze the relationship between the completeness of its facilities by the number of visits each year. By knowing everything about this tourist village, is expected to be a lesson for people who have great potential but this potential has not been maximized.